PRODUCTIVITY IN RAILWAY TRANSPORT - Romanko, V. I.; Romanko, O. V. (Science and Transport Progress, 2008)
The labor productivity on railway transport ofUkraine, the methods of its calculation at facilities and the factors affecting its changes are considered in the article.